Tracking MPC with non-convex steady state admissible sets. Issue 20 (2018) - Cotorruelo, Andres; Limon, Daniel; Garone, Emanuele; Ramirez, Daniel R.
Abstract: In this paper, we propose an extension to the existing Model Predictive Control scheme for tracking. This extension is able to provide a solution for the case where the set of steady-state admissible outputs is non-convex. This is achieved by means of a transformation that maps the output set into a convex set. In the proposed scheme, the cost function and constraints of the usual tracking MPC are modified, so that the controller can drive the system to any point in the admissible steady-state domain without violating any constraints. The paper discusses the feasibility and stability of the proposed approach and a final simulation demonstrates the effectiveness of the approach.